An examination of the role of food retailers in alleviating the Covid-19 food crisis through effective food waste management: A Case Study on Woolworths Food Group South Africa - Ovadia, Michaela Rebecca (The IIE, 2020)
Food waste is a growing concern worldwide that is worsening as the global population and economy grow (Papargyropoulou, Lozano, Steinberger, Wright & bin Ujang, 2014). Looking at the current climate in South Africa and the harsh impacts of the Covid-19 pandemic, food accessibility has worsened substantially, making poverty and hunger a larger concern than the virus itself (Investec, 2020). The excessive amount of food waste, alongside the food accessibility crisis, highlights that food waste management is essential to mitigate the high rates of hunger that have increased with the growth in unemployment as a result of Covid-19 (Matiase, 2020; 2oceansvibe, 2018). Although food waste management is a topic that has already been explored, the drastic increase in hunger in South Africa as a result of the Covid-19 pandemic makes it imperative to explore how large food retailers like Woolworths have implemented food waste management methods to improve food accessibility at this time. This study suggests that investigating how Woolworths manages food waste will create greater awareness for Woolworths and similar companies to further their food waste management efforts in-store. Data were collected and analysed from the interview with two senior managers at Woolworths’ head office as well as Woolworths’ 2019 Good Business Journey report. Exploring and investigating ways in which food retailers implement food waste management practices will provide opportunities for Woolworths and other retailers to alleviate the food accessibility crisis in South Africa, which has worsened dramatically due to Covid-19.
Keywords: Food accessibility; Meaningful brands; Conscious recycling labels; Food Waste Hierarchy Framework